Evaluation of the anticoagulant effect of Saphia Alkali K90 in an experimental thrombosis model - Anh, Pham Thi Van; Chung, Nguyen Thi; Tam, Tran Thi Minh; Thanh, Tran Van; Hang, Vu Viet; Chung, Nguyen Tien; Loan, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2026)
The study aimed to investigate the anticoagulant effects of Saphia Alkali K90 in a rat model of lipopolysaccharide-induced thrombosis. Saphia Alkali K90 and rivaroxaban were administered orally for seven consecutive days. Two hours after the final administration, LPS (3 mg/kg) was injected via the tail vein to induce thrombotic changes. Blood samples were collected four hours later to assess coagulation. The results showed that Saphia Alkali K90 at 54 ml/kg/day produced a significant anticoagulant effect, evidenced by increased platelet count and fibrinogen concentration, as well as a significant prolongation of the activated partial thromboplastin time compared to the vehicle-treated group (p < 0.05). In contrast, Saphia Alkali K90 at 27 ml/kg/day showed a non-significant tendency toward similar changes (p > 0.05). In conclusion, SAK90 at 54 ml/kg/day exerted an anticoagulant effect in rats with LPS-induced thrombosis.